A Review and Probabilistic Analysis of Limit State Functions of Corroded Pipelines - Mustaffa, Zahiraniza (The International Society of Offshore and Polar Engineers (ISOPE), 2010)
This paper introduces a new approach in developing a limit state function used in a probabilistic method when analyzing an aging structure. The so called dimensionless limit state function was formulated from the application of the well known Buckingham π theorem coupled with the multivariate statistics. Its application was proven to be an ideal solution for aging pipelines subjected to corrosions. Not only that, this method has the advantage to incorporate the circumferential defect (w) term, a parameter which is normally neglected by the existing codes and most limit state functions developed by literatures. For this, a review on the past and present limit state function developments was first discussed. The inclusion of w term in the dimensionless limit state function was found to be reasonable as it represented the total defect volume rather than its area (as seen) from the longitudinal view. Results from this new approach were compared with the literatures. Its favorable results may overcome the conventionality of the existing codes and this is something to ponder.